Síndrome de Cotard: uma investigação psicanalítica - Malucelli, Dayse Stoklos (2007)
The scope of this study developed at the Núcleo de Psicanálise do Laboratório de Psicopatologia Fundamental da Pontifícia Universidade Católica de São Paulo (Psychoanalysis Center of the Psychopathology Laboratory at the Catholic University of São Paulo) is the review of a certain type of delirium, the negation delirium, also known as Syndrome of Cotard and it emphasizes the symptomatology that is present in most melancholies and schizophrenias. The references found in this field may lead to sinuous ways, because of its only slightly approached complexity. In order not to withdraw from the University compass, some aspects were trimmed according to the theory sustaining this process. There is a clinical case reported that is compatible to the Syndrome of Cotard - this name given in honor of the nineteen century French doctor Jules Cotard. From Cotard s reports on his patients at the Hôpital Salpêtrière, it is possible to approach the current events, once in spite of the latter numerous medications, the patients recovering and the outreaching of the disease are not yet achieved. The negation deliria have a history in Psychiatry, in particular the XIX century French history and include the work of Jules Cotard, his five short, dense and heavy clinical cases that are illustrative and punctual. This situation is repeated for his contemporary alienists of the same level, such as Seglas, Camuset, Régis, and Nina-Rodrigues. This work describes the main manifestations of the syndrome, such as micromania, macromania, no adherence body sphericity, the mirror stage and their peculiarities in Cotard. It also approaches the concept of hypochondria, a recurring manifestation and background to other superposed manifestations. The sadness observed in Cotard s melancholic individuals shows to be pertinent and significant the reports by Dante and father Antonio Vieira, for melancholia does not include nor mixes with sadness. Some of literature examples confirm Freud s thought on poets and writers, who know more about the soul s pains than psychoanalysts do. In this work, classical authors like Freud and Lacan and some of their successors are examined. Furthermore, the chronicity of this type of syndrome is analyzed that makes it possible to the clinical hearing in psychoanalysis, and overthrows the ideal of furor curandis, once the individual who is analyzed under Cotard will always say this is not the case. His denial, however, would allow another negation: the closure of the issue. As in other areas where the alternatives for the great evils in humanity are searched, a new horizon may leave a challenge with new points of view to be established by those who are interested in this difficult but instigating clinical issue